The present landscape of greenhouse gas emissions in maritime transportation - Mindroiu, Bianca Ioana; Scurtu, Ionuț Cristian; Bosneagu, Romeo (Technium Sustainability, 2024)
This article presents the evolution of greenhouse gas emissions from different types of ships. Since the total decarbonization of the maritime sector is being pursued worldwide, it is important to analyse which are the ships with the highest greenhouse gas emissions and to present methods by which these values ​​can be reduced. Thus, starting from the current level of greenhouse gas emission levels, an analysis was started that follows their evolution depending on the type of ship and the fuel used. The results presented in the study have the role of identifying the major problems in this sector and support the formulation of solutions that can reduce values.